Will the southern African west coast fog be affected by future climate change? Results of an initial fog projection using a regional climate model - Haensler, Andreas; Cermak, Jan; Hagemann, Stefan; Jacob, Daniela (ERDKUNDE, 2011)
We present an initial study to project the long-term development of fog occurrence along the southern African west coast. For this purpose, we implemented a basic fog diagnostic scheme based on liquid water content into the regional climate model REMO. The validation of the fog diagnostic scheme is conducted using satellite-derived low cloud information as well as local station observations. The validation reveals that REMO is able to adequately represent the major fog characteristics in the region. The observed strong fog gradient from the coast to the regions further inland is correctly simulated by the model. Also, the seasonal as well as diurnal fog distribution characteristics are captured by REMO. However, some deficits still remain in the absolute amount of simulated fog days. These deficits can mainly be attributed to the coarse vertical resolution of the model as well as to the simple fog diagnostics approach chosen. Regarding the long-term development of fog, two 20-year time slice simulations for a control (1981 to 2000) and a future (2081 to 2100) period following the A1B emission scenario were conducted. The model generally projects a slight increase in the number of fog days for the coastal areas and a slight decrease for the regions located further inland. Especially the latter has the potential to exacerbate the existing water scarcity in the region.